2022
DOI: 10.1039/d1bm01722e
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-stimulated mesenchymal stem cell-derived exosomes loaded by adhesive hydrogel for effective angiogenic treatment of spinal cord injury

Abstract: Implantation of hypoxia-stimulated mesenchymal stem cell-derived exosome encapsulated in an adhesive hydrogel induced pro-angiogenic spinal cord repair through transporting HIF-1α and upregulating vascular endothelial growth factor expression in recipient endothelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 52 publications
0
33
0
Order By: Relevance
“…A significant rise in protein synthesis of EGF, fibroblast growth-factors, VEGF/VEGF receptors (VEGF-R), Ang-1, and angiopoietin receptor tyrosine kinase with immunoglobulin-like and EGF-like domains 1 (Tie-1) were shown in grafted animals, 30 d after transplantation[ 106 ]. Inclusion in hydrogels that allow local release of EV with high angiogenic capacity has also been used for treatment of spinal-cord injuries[ 107 ]. One of the proteins that has been found to be over synthesized in MSC-derived EV under hypoxia, compared to those obtained in normoxia, is jagged-1 (JAG1).…”
Section: Therapeutic Potential Of Ev Derived From Msc Preconditioned ...mentioning
confidence: 99%
“…A significant rise in protein synthesis of EGF, fibroblast growth-factors, VEGF/VEGF receptors (VEGF-R), Ang-1, and angiopoietin receptor tyrosine kinase with immunoglobulin-like and EGF-like domains 1 (Tie-1) were shown in grafted animals, 30 d after transplantation[ 106 ]. Inclusion in hydrogels that allow local release of EV with high angiogenic capacity has also been used for treatment of spinal-cord injuries[ 107 ]. One of the proteins that has been found to be over synthesized in MSC-derived EV under hypoxia, compared to those obtained in normoxia, is jagged-1 (JAG1).…”
Section: Therapeutic Potential Of Ev Derived From Msc Preconditioned ...mentioning
confidence: 99%
“…Previous studies have shown that exogenous hypoxic treatment prevents the degradation of HIF-1α and favors the accumulation of cellular HIF-1α in a time-dependent manner, followed by their integration into the exosomes. [57,58] Therefore, we hypothesized that hypoxic treatment might increase the content of HIF-1α in E-Exos, which could achieve self-presentation to elevate its endogenous level. To confirm the abundance of HIF-1α protein in E-Exos, the expression of HIF-1α in exosomes was analyzed under different induction conditions by using an ELISA kit (Figure S37a, Supporting Information), demonstrating that hypoxia and TNF-α/hypoxia stimulations induce massive aggregation of HIF-1α in E-Exos, supporting the idea that HIF-1α-enriched E-Exos contributes to endogenous HIF-1α accumulation in wound sites.…”
Section: Suppression Of Oxidative Stress Inflammation and Promotion O...mentioning
confidence: 99%
“…Fortunately, MSC-derived exosomes (MSC-EXOs) secreted by MSCs have similar therapeutic benefits for immune modulation when injected into acute SCI lesions 1620 . Previous studies have shown that MSC-EXOs immobilized in a peptide-modified adhesive hydrogel transplanted into an SCI lesion during the acute phase could mitigate the SCI microenvironment and promote functional recovery 21,22 . However, the retention time of MSC-EXOs in spinal tissue might not be long enough for them to exhibit their optimal therapeutic effects.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Previous studies have shown that the transplantation of MSC-EXO immobilized in a peptide-modified adhesive hydrogel into an SCI lesion during the acute phase could mitigate the SCI microenvironment and promote functional recovery. [10] However, the retention time of MSC-EXO in the spinal tissue might not be long enough to exhibit their optimal therapeutic effects. The neuroinflammation and neuronal apoptosis caused by SCI could continue for a couple of weeks or even longer, [11] but MSC-EXO could not be continuously delivered into the lesion of SCI by these methods.…”
Section: Introductionmentioning
confidence: 99%